Early Femoral Insufficiency Fractures After Primary Total Knee Arthroplasty - T. David Tarity, MD; William Xiang, BS; Paul Guirguis, BA; Elizabeth B. Gausden, MD; Brian P. Chalmers, MD; Friedrich Boettner, MD; Alberto V. Carli, MD; Peter K. Sculco, MD (Arthroplasty Today, 2023)
Background: Periprosthetic femur fracture following total knee arthroplasty (TKA) is a devastating complication. Although trauma-related periprosthetic femur fractures have been well studied, early atraumatic insufficiency periprosthetic fractures (IPFs) are gaining attention. We present the largest IPF series to date to better understand and prevent this complication. Methods: A retrospective study of all patients who underwent a revision surgery for periprosthetic fracture within 6 months of primary TKA between 2007 and 2020 was performed. Patient demographics, preoperative radiographs, implant details, and fracture radiographs were reviewed. Alignment measurements and fracture characteristics were assessed. Results: Sixteen patients met criteria (rate 0.05%), and 11 had posterior-stabilized TKAs. The mean age was 79 years, mean body mass index was 31 kg/m2, and 94% (15/16) were female. Seven (47%) patients had a confirmed history of osteoporosis. IPF occurred on average 4 weeks (range, 4 days-13 weeks) after the index TKA. Overall, 12 of 16 (73%) had preoperative valgus deformities, and 11 patients (10 valgus, 1 varus) had preoperative deformities >10 degrees. A characteristic radiographic appearance of femoral condylar impaction and collapse was noted in 12 of 16 cases (75%); 11 of these 12 fractures (92%) involved the unloaded compartment based on preoperative varus/valgus deformity. Conclusions: Patients who developed IPFs were most commonly elderly, obese women with osteoporosis and severe preoperative valgus deformities. The apparent mechanism of failure was overloading of previously unloaded osteopenic femoral condyle. In high-risk patients, the use of a cruciate-retaining femoral component or a femoral stem for a posterior-stabilized femur may be considered to help avoid this catastrophic complication.